Exceptional reduction of the plastid genome of saguaro cactus (Carnegiea gigantea): Loss of the ndh gene suite and inverted repeat. Issue 7 (1st July 2015) - Sanderson, Michael J.; Copetti, Dario; Búrquez, Alberto; Bustamante, Enriquena; Charboneau, Joseph L. M.; Eguiarte, Luis E.; Kumar, Sudhir; Lee, Hyun Oh; Lee, Junki; McMahon, Michelle; Steele, Kelly; Wing, Rod; et al.
Abstract : Premise of the study: Land‐plant plastid genomes have only rarely undergone significant changes in gene content and order. Thus, discovery of additional examples adds power to tests for causes of such genome‐scale structural changes. Methods: Using next‐generation sequence data, we assembled the plastid genome of saguaro cactus and probed the nuclear genome for transferred plastid genes and functionally related nuclear genes. We combined these results with available data across Cactaceae and seed plants more broadly to infer the history of gene loss and to assess the strength of phylogenetic association between gene loss and loss of the inverted repeat (IR). Key results: The saguaro plastid genome is the smallest known for an obligately photosynthetic angiosperm (∼113 kb), having lost the IR and plastid ndh genes. This loss supports a statistically strong association across seed plants between the loss of ndh genes and the loss of the IR. Many nonplastid copies of plastid ndh genes were found in the nuclear genome, but none had intact reading frames; nor did three related nuclear‐encoded subunits. However, nuclear pgr5, which functions in a partially redundant pathway, was intact. Conclusions: The existence of an alternative pathway redundant with the function of the plastid NADH dehydrogenase‐like complex (NDH) complex may permit loss of the plastid ndh gene suite in photoautotrophs like saguaro. Loss of these genes may be a recurring mechanism for overall plastid genome size reduction, especially in combination with loss of the IR.